Spurious prospective effect of physical activity on problematic smartphone use: a simulated reanalysis and comment on Zhao et al. (2024) - Sorjonen, Kimmo; Melin, Bo (Frontiers in Psychology, 2024)
Based on findings from analyses with cross-lagged panel models, Zhao et al. concluded that physical activity can reduce problematic smartphone use (PSU) among adolescents. Here, we simulated data to resemble the data used by Zhao et al. We used triangulation and fitted complementary models to the simulated data and found contradicting decreasing, increasing, and null effects of initial physical activity on subsequent change in PSU. These divergent findings suggest that it is premature to assume a decreasing effect of physical activity on PSU and the conclusion by Zhao et al. in this regard can be challenged. It is important for researchers to be aware that correlations, including adjusted cross-lagged effects, do not prove causality in order not to overinterpret findings, something that appears to have happened to Zhao et al. We recommend researchers to triangulate by fitting complementary models to their data in order to evaluate if observed effects may be due to true causal effect or if they appear to be spurious.